Cartel damages in lowest price english auctions with endogeneous entry - Lima, Lucas Ferreira Matos (2018)
This thesis study the damages a cartel can generate on public procurements. Specifically, we study collusion on a lowest price English auction with endogeneous entry. We show that assuming endogeneous entry with a collusive behavior can generate two important outcomes on auctions: (i) alocative inefficiency and (ii) the prices of auctions lost by the cartel can be affected. So this work contributes with the recent discussion antitrust authorities are having on the relevance of calculating cartel damages. We also study a medicine cartel case that operated in Sao Paulo public procurements and use reduced form models to find evidence of it’s presence. Lastly, we use equilibrium conditions from our model to create counterfactual scenarios of the medicine cartel case. Doing simulations, we find the cartel generated an overcharge of 10%, but did not created alocative inefficiency.